Kinerja Aparatur Sipil Negara pada Dinas Pendidikan Provinsi Sulawesi Tengah - Dewi Hastuty; Abdul Rivai; Mashuri Mashuri (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study aims to determine the performance of State Civil Apparatus at the Central Sulawesi Provincial Education Office. This study uses a qualitative data method. The research location is the Central Sulawesi Provincial Education Office. The theory used in this study is the theory put forward by Robbins. Informants in this study numbered 6 (six) people. Data obtained in this study from the results of observation, interviews, and documentation. The data analysis methods are Data Collection, Data Condensation, Data Presentation, and Conclusion Drawing/Verification.The results of this study indicate that civil servant performance has shown positive progress, but several structural, competency, and organizational culture barriers remain that need to be addressed. If improvements are implemented systematically, civil servant performance has the potential to significantly improve, particularly in facing the increasingly complex demands of educational administration in the digital age.